Music making software programs for children from ages five to twelve - Tulikari, Aki (2010)
This research classifies the qualities in the existing music creation software programs that enable them to be operated by young users. This is done through comparison of the literature on musical development of children and the examination of the existing software. For the research were selected three fundamentally different pieces of music creation software that potentially provide a wide variety of features. The selected programs are GarageBand, Songsmith and Groovy Music. Each of the three programs has its own strengths in benefiting children s musical development in different ages. What all programs share is the ease of use and a clear interface. Icons of the functions help navigating the software with less effort. Each of the programs offer an easy start up, after which the user can find more settings and possibilities as he or she advances. The three pieces of software described in the study each have something new to offer for the field of music education. The ease of creating new music without the conventional know-how or ability to play an instrument can be very inspiring for users of any age. The software programs may also work as a gateway for other musical interests. It is also possible to study music theory independently with a help of software program.